Family ministry field guide : how your church can equip parents to make disciples - Jones, Timothy P. (Timothy Paul) (Indianapolis, Ind. : Wesleyan Pub. House, 2011)
"Scripture calls parents to train their children in the faith and to nurture their children's souls. Yet few parents actively engage in their children's spiritual development. How can churches best equip families to engage in their divine calling to disciple their children? Family ministry expert Dr. Timothy Paul Jones guides church leaders to develop a ministry system that equips parents to be the primary faith-trainers in their children's lives, moving beyond mere programming into a deeper spiritual life at home, within the church, and beyond. This resource is for leaders in the trenches--those who: see parents disengaging from their children's spiritual development; see too many students leave for college and drop out of church; have heard of 'family ministry,' and just want to know more; or are frustrated with programmed ministries that fail to produce results. Based on solid research, this field guide unpacks how real-life churches can narrow the gap between present reality and the biblical ideal of faith-nurturing families" -- Publisher description.
What families in your church are doing, and not doing, when you're not looking -- What family ministry is and why it's worth it -- Why not to do family ministry -- How to find the right motivation -- Discover who your children really are -- The split in God's story line -- We're supposed to do that at home? -- A matter of training and a matter of time -- Providing what parents really need -- Killing the one-eared Mickey Mouse.
Includes bibliographical references (p. [219]-222)
Keywords: Church work with families; Christian education of children; Christian education -- Home training